Exploring the relationship between service quality of technology transfer offices and researchers’ patenting activity (2020)
This article examines how the perceived quality of the service provided by technology transfer offices influences researchers’ likelihood to patent their research results. A novel three-dimensional model is proposed aiming at analyzing the combined effect of service quality perceptions—service reliability, infrastructures and staff—alongside with factors that capture the university's regulatory framework and the profile and experience of the researcher. Results suggest that the profile of the researcher is much more critical for driving patenting activity than the quality of the services offered by the technology transfer office (TTO). However, the effect of the service quality delivered by the TTO is stronger when the researcher has less experience compared to researchers with a consolidated career.